Perancangan dan Impelementasi QoS Di Mikrotik Menggunakan Metode HTB (Studi Kasus SMP MBS Al Karimah Cibadak) - Hamudi Alamsyah; Somantri (LPPM UNIKA Santo Thomas, 2022)
SMP Muhammadiyah Boarding School is a boarding school where students are required to live in a dormitory that has been provided. In addition to students, there are coaches whose job is to guide students after their teaching and learning activities are completed. In carrying out their activities in addition to guiding students, coaches really need an internet network connection to meet their needs and interests in finding things needed on the internet. In order to avoid problems in using the internet network from an ISP, it is necessary to have bandwidth management that can regulate the speed of internet connections so that it is more equitable in the distribution of internet bandwidth. If a LAN network without bandwidth usage management may often occur bandwidth struggles between client 1 and other clients. LAN (Local Area Network) is a computer network that is connected to a computer server using a certain topology, usually used in the area of one building or area not more than one km away [4]. With the problems as above, the authors conducted research and made a QoS Design and Implementation in Mikrotik Using the HTB Method (Case Study of SMP MBS AL KARIMAH). The author has analyzed that the topology used in SMP MBS AL KARIMAH is a Star topology with 1 Telkom ISP modem which is directly connected to the switch and from the switch to the client. This design is done by using a Mikrotik Router and a Winbox application for a remote Mikrotik router. Mikrotik is a Linux base operating system designed specifically for networking purposes [13]. In addition, MikroTik Router has several features such as authentication, authorization, client accounts, routing, mpls, Queues, firewalls, IP Telephony which allows Voice over IP (VoIP) [15].